Pengaruh Penggunaan Media Kartu Kata Terhadap Kemampuan Membaca Permulaan pada Siswa Kelas I SDN 104181 Sunggal Kanan - Mastari Ramadhani (Tematik: Jurnal Penelitian Pendidikan Dasar, 2022)
Reading in everyday life is very important, because by reading we can find out written information. Often read, people can master a lot of vocabulary, and can learn various types or models of sentences. Therefore, to improve reading it must be taught from an early age. The benefits that can be obtained from teaching children to read from an early age include: increasing children's vocabulary, improving communication skills, and being able to create their imagination. This study aims to determine the effectiveness of using word cards to improve children's early reading skills in the experimental class at SDN 104181 Sunggal Kanan. To achieve the above objectives, a quantitative research approach is used. The type of experimental research is one group pretest posttest. In this study, researchers took a sample of 24 children in the experimental class and 25 children in the control class at SDN 104181 Sunggal Kanan. With data collection techniques using an assessment instrument. Data analysis using t test. The results of this study indicate that the learning outcomes in the experimental class are higher than those in the control class. This conclusion is based on the final results of the average children, where the average pretest of children in the experimental class (before treatment) was 6.375 out of 24 children, while the average of children in the posttest results was 9.167. While in the control class, the average pretest of children ) was 5.8 out of 25 children, and the average of children on the posttest results was 6.44. In addition to the students' average results, the results of the t-test were also obtained, namely the t-count value obtained a significance value (sig.) 0.000 <0.05. So it can be concluded that Ho is rejected and Ha is accepted, which means that there is an effective use of word cards to improve early reading skills.